Convergence at Wellesley College - Fox, Anthony Ryan (Kansas State University, 2009)
The challenges of the 21st Century will require a force of bright, innovative thinkers and leaders, researchers and scientists. Academic Institutions all across the world must prepare these future leaders. Creating physical spaces that manifest an institutions mission is critical. This study seeks to find a paradigm for the 21st Century campus; to create a more collegial, engaging, influential environment to study, research and learn. Each academic institution is guided by a mission that shapes curricula and informs scholarship. It is the campus environment that provides the physical space for study and shapes interactions between students and faculty and creates a meaningful community of learning. The goal of the project is to create spaces which encourage strong interaction, collaboration and the creation of ideas. The intersection and convergence of knowledge at Wellesley College exemplifies the dynamic campus of the 21st Century. The study will connect the campus community through the creation of vibrant, dynamic campus spaces along its waterfront, furthering the goals —engagement, collaboration and experience—while enhancing the immutable regionalism of Wellesley College. Convergence at Wellesley College aspires to create spaces which inspire, encourage and assist in the education of leaders who will confront the worlds greatest challenges.
Keywords: Campus design; Wellesley college; Waterfront design; Engagement; Mission; Collaboration; Landscape Architecture (0390)